Interfused nanofibres network in scalable manufacturing of polymeric fibres via multi‐nozzle electrospinning. (1st April 2018) - Al‐Mezrakchi, Ruaa Yaseen Hammoudi; Naraghi, Mohammad
Abstract : The authors have studied the formation of an interfused network of nanofibres in multiple‐needle electrospinning, a phenomenon reported here for the first time to their knowledge. Their study points to the significant role of humidity in controlling the morphology of nanofibre ensemble in electrospinning: when the humidity is sufficiently low, entangled mat of nanofibres with little or no interfusion between them are formed. However, at sufficiently high humidity, electrospun jets diffused into each other, forming a network of interfused fibres. The onset of jet interfusion during electrospinning is notable with naked eyes. The humidity that corresponds to the onset of the jet interfusion is referred to as the humidity threshold. They studied the formation of the nanofibre interfusion, and the relationships between humidity threshold and nanofibre diameters with processing parameters. They then presented a theory which explains the formation of the interfused network of fibres in terms of water condensation on the jets due to evaporative cooling. The presented approach allows for direct (one‐step) fabrication of high surface area interfused nanofibre network without post‐processing. This unique fibre structure can have significant implications on fibre applications for air and water filtering, where the structural integrity of the filter matters.